Secondary aerosol formation in winter haze over the Beijing-Tianjin-Hebei Region, China - Shang, D.; Peng, J.; Guo, S.; Wu, Z.; Hu, M. (Frontiers of Environmental Science and EngineeringFrontiers of Environmental Science and Engineering, 2021)
Severe haze pollution occurs frequently in the winter over the Beijing-Tianjin-Hebei (BTH) region (China), exerting profound impacts on air quality, visibility, and human health. The Chinese Government has taken strict mitigation actions since 2013 and has achieved a significant reduction in the annual mean PM2.5 concentration over this region. However, the level of secondary aerosols during heavy haze episodes showed little decrease during this period. During heavy haze episodes, the concentrations of secondary aerosol components, including sulfate, nitrate and secondary organics, in aerosol particles increase sharply, acting as the main contributors to aerosol pollution. To achieve effective control of particle pollution in the BTH region, the precise and complete secondary aerosol formation mechanisms have been investigated, and advances have been made about the mechanisms of gas phase reaction, nucleation and heterogeneous reactions in forming secondary aerosols. This paper reviews the research progress in aerosol chemistry during haze pollution episodes in the BTH region, lays out the challenges in haze formation studies, and provides implications and directions for future research. [Figure not available: see fulltext.]. © 2020, Higher Education Press.
Keywords: Aerosol chemistry; aerosols; air quality; Aqueous reaction; Beijing-tianjin-hebei regions; chemical mechanism; Chemical reactions; Chinese Government; gas-phase reactions; heterogeneous reactions; Particle pollution; Phase interfaces; Photochemical reaction; PM2.5 concentration; Pollution control; Regional haze; secondary aerosol formation; secondary aerosols; Sulfur compounds